Increasing frequency of therapy by software-based treatment of naming ability in people with aphasia: a preliminary study. - Atalık, Güzide; Kulak Kayıkcı, Maviş Emel (Disability & Rehabilitation: Assistive Technology, 2025)
This study aimed to explore the effect of new software targeting naming deficits in Turkish-speaking people with aphasia. The study included seven Turkish people with aphasia. These participants took the Aphasia Language Assessment Test (ADD), Turkish Picture-Naming Test (T-RAT), and Technology Familiarity Assessment, and the words for therapy were determined. The selection of categories and words for inclusion in the application was based on the frequency and typicality features. The 12-week speech-language treatment sessions were divided into two sections. During the first six weeks, a speech-language pathologist (SLP) used the software to train people. After the first part, the SLP applied the T-RAT. Participants utilized the software at home in the second part. All participants took the ADD, T-RAT, and Software Evaluation Questionnaire following the second part. Participants' naming abilities improved in all tests. Both therapy sessions with the SLP and those in which participants used the program independently demonstrated this improvement. Participants also reported high levels of treatment satisfaction. Cueing hierarchy approaches used in the software helped to improve naming skills in people with aphasia (PWA), independent of type, stage, or severity of aphasia. The findings of this study indicate that both sessions directed by an SLP and independent use of the software by participants can positively impact the therapy process with the developed software. IMPLICATIONS FOR REHABILITATION: Cueing hierarchy approach is commonly used to treat word-retrieval impairments in people with aphasia (PWA). Several studies in the literature report that integrating semantic and phonological approaches is beneficial in therapeutic interventions. Different levels of improvement were observed in the naming skills of PWA when the cueing hierarchy methods were presented via software. This study has shown that many PWA could improve their naming skills via software-based therapy. It was determined that working at home with the application could effectively contribute to the therapy process. Consequently, enhanced accessibility to therapeutic interventions will be facilitated, resulting in an increased frequency of treatment sessions. With rapid technological development, the use of software applications in speech and language therapies is increasing. An application that included cueing hierarchy techniques was created for naming therapy with Turkish PWA in this study. The PWAs' naming abilities showed improvement, and they stated satisfaction with using the software in their therapeutic processes.